The Correlation Between Community Health Cadres Knowledge and the Role in Preventing COVID-19 in Teluk Village - Salsabila Thalita Dama Agatha; Diyah Yulistika Handayani (Proceedings Series on Health & Medical Sciences, 2021)
Background : According to data from Banyumas Health Agency(2021), Teluk Village was once a red zone because there were 14 confirmed cases of COVID-19. Therefore, several activities involving the community, including Integrated Health Services Post, were suspended. During the pandemic, the majority of mothers are worried to take their children to health facilities to be immunized, whereas immunization is very important. In order to reduce parents' worries, the role of Community Health Cadres(CHCs) is needed in providing information related to safe immunization procedures. Objective : The purpose of this study was to figure out the correlation between CHCs knowledge and the role in preventing COVID-19. This was quantitative research with a cross-sectional approach. Method : This research has been carried out on 64 CHCs in Teluk Village. Percentages and chi-square test analysis were employed to answer the research problems. Results : The results indicated that most of the respondents graduated from high school and were of productive age. In addition, most of them have become CHCs for 15 years. 46.9% of the respondents had a good level of knowledge about COVID-19, while 53.1% had a moderate level. The role of most of the cadres in preventing COVID-19 was in the optimal category (60.9%), while the rest (39.1%) was not optimal. Conclusion : The p-value was 0.001(0.05) therefore it can be concluded that there is a correlation between cadres' knowledge about COVID-19 and the roles in preventing the disease.